The electrothermal impact on a contact metal-semiconductor: applications to the germanium–silver system - Skvortsov, Arkadiy; Khripach, Nikolay A; Papkin, Boris A; Pshonkin, Danila E (Microelectronics international, 2018)
Purpose This study aims to examine the electromigration processes resulting from thermal overloads of semiconductor devices. While in operation, parts of such devices can heat up to 330°C for a short period, resulting in the emergence of molten zones and the devices’ inevitable degradation. Therefore, this study examines the mechanisms behind the formation and migration of silver-based molten zones in bulk germanium and on its surface. Design/methodology/approach Experimental data concerning the correlation between the migration velocities of the inclusions and their sizes are obtained. Findings By comparing these experimental data with known electromigration models, it is concluded that inclusions move through the mechanism of melting and crystallization. The dynamics of Ge–Ag zones in the volume of a germanium crystal are compared to those on its surface and accelerated electromigration on the surface of the crystal is observed. This increased migration velocity is shown to be associated with additional contributions of the electrocapillary component. Originality/value The results of this study can be used to calculate the operating modes of semiconductor power devices under intense heat loading.